How dislocation and professional anxiety influence readiness for change during the implementation of hospital-based home care for children newly diagnosed with diabetes - an ethnographic analysis of the logic of workplace change - Gabriella Nilsson; Kristofer Hansson; Irén Tiberg; Inger Hallström (BMC, 2018)
Abstract Background In 2013-14, the evidence based care model Hospital-based Home Care for children newly diagnosed with diabetes was implemented at a large paediatric diabetes care facility in the south of Sweden. The first step of the implementation was to promote readiness for change among the professionals within the diabetes team through regular meetings. The aim was to analyse the implicit facilitators and barriers evident on a cultural micro level in discussions during the course of these meetings. What conceptions, ideals and identities might complicate, or facilitate, implementation? Methods A case study was conducted during the implementation process. This article draw on ethnographic observations carried out at team meetings (n = 6) during the introductory element of implementation. From a discourse theoretical perspective, the verbal negotiations during these meetings were analysed. Results Three aspects were significant in order to understand the dislocation during this element of implementation: an epistemological disagreement that challenged the function of information within care practice; a paradoxical understanding of the time-knowledge intersection; and expressions of professional anxiety. More concretely, the professionals exhibited an unwillingness to give up the opportunity to provide structured, age-independent information; a resistance against allowing early discharge; and a professional identity formed both by altruistic concern and occupational guardiancy. The findings suggest the necessity of increased awareness of the conceptions and ideals that constitute the basis of a certain professional practice; a deeper understanding of the cultural meaning that influences care practice within a specific logic in order to predict in what way these ideals might be challenged by the implemented evidence. Conclusions Our main contribution is the argument that the implemented evidence in itself needs to be examined and problematized from a cultural analytical perspective before initiation in order to be able to actively counter negative connotations and resistance.